2003
DOI: 10.1002/glia.10215
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular calcium waves in cultured enteric glia from neonatal guinea pig

Abstract: Enteric glia are important participants in information processing in the enteric nervous system. However, intercellular signaling mechanisms in enteric glia remain largely unknown. We postulated that intercellular calcium waves exist in enteric glia. Primary cultures of enteric glia were isolated from neonatal guinea pig taenia coli. Intracellular calcium in individual cells was quantified with fura-2 AM microfluorimetry. Single-cell stimulation was performed with a micromanipulator-driven glass pipette. Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 16 publications
3
72
0
1
Order By: Relevance
“…Much like in CNS astrocytes, propagating calcium waves have been reported in cultured enteric glia in response to mechanical stimulation (Zhang et al, 2003). Furthermore, guinea pig enteric glia express mGluR5 receptors, raising the possibility that they may respond to glutamate (Nasser et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Much like in CNS astrocytes, propagating calcium waves have been reported in cultured enteric glia in response to mechanical stimulation (Zhang et al, 2003). Furthermore, guinea pig enteric glia express mGluR5 receptors, raising the possibility that they may respond to glutamate (Nasser et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…44 In fact, experimental human and animal studies have shown that enteric glial cells may also be involved in intestinal inflammation, 45,46 enteric neurotransmission [47][48][49] and, importantly, are essential for the homeostasis of enteric neurons. 50 With respect to this last aspect, a recent study showed that enteric glia disruption may alter the neurochemical coding of enteric neurons in an experimental animal model.…”
Section: Discussionmentioning
confidence: 99%
“…Most EGC within enteric ganglia are contacted by vesiculated nerve processes with presynaptic specializations [35], and respond to transmitters released by these terminations by expressing a series of receptors for neurotransmitters and neuromodulators [36][37][38][39]. Thus, EGC can modulate enteric neural circuits in several ways, such as by supplying neurotransmitters precursors to neurons [40,41], terminating the actions of neurotransmitters from synapses [42,43], and through the generation of neuroactive compounds [44]. In addition, EGC are needed to assure survival of the enteric neurons, as demonstrated by the experimental ablation of the intestinal glial network [45].…”
Section: Interlinks Of Enteric Glial Cells With Enteric Neurons and Nmentioning
confidence: 99%